Structuring of proverbs and sayings into semantic combinations (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the proverbs and sayings as the ancient genres of Kazakh oral folk art. A detailed story, explanation, memory about a legend which explains the origin of these sayings are required for clarifying the origin and meaning of a particular proverb. The article presents a brief characterization of proverbs and their ability to achieve a high aesthetic and philosophical level and withstand the selection for many centuries and millennia. The attention is also drawn to the fact that Kazakh people always gave preference to the art of words, proverbs and sayings that are part of a priceless treasure of Kazakh folklore.
Keywords: proverbs; sayings; combination of meaning; direct meaning; indirect meaning; genre; oral folk art.